2017
DOI: 10.1155/2017/3436943
|View full text |Cite
|
Sign up to set email alerts
|

Could Perinatal Asphyxia Induce a Synaptopathy? New Highlights from an Experimental Model

Abstract: Birth asphyxia also termed perinatal asphyxia is an obstetric complication that strongly affects brain structure and function. Central nervous system is highly susceptible to oxidative damage caused by perinatal asphyxia while activation and maturity of the proper pathways are relevant to avoiding abnormal neural development. Perinatal asphyxia is associated with high morbimortality in term and preterm neonates. Although several studies have demonstrated a variety of biochemical and molecular pathways involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 60 publications
(87 reference statements)
0
16
0
Order By: Relevance
“…Different studies showed that the survivors of asphyxia developed hypoxic-ischemic encephalopathy[ 4 , 14 , 15 ], post-traumatic stress disorders[ 16 ], neurologic disability[ 17 ], low cognitive functions[ 18 ], and neurological sequel[ 19 ]. A certain experimental study also revealed that nearly 25% of the newborns who survived birth asphyxia developed neurological disorders, such as cerebral palsy and certain neurodevelopment and learning disabilities[ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different studies showed that the survivors of asphyxia developed hypoxic-ischemic encephalopathy[ 4 , 14 , 15 ], post-traumatic stress disorders[ 16 ], neurologic disability[ 17 ], low cognitive functions[ 18 ], and neurological sequel[ 19 ]. A certain experimental study also revealed that nearly 25% of the newborns who survived birth asphyxia developed neurological disorders, such as cerebral palsy and certain neurodevelopment and learning disabilities[ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…This rat model of global asphyxia involves the submersion of pup containing uterine horns in a water bath immediately after caesarean section, mimicking delayed labor. This method presents other translational advantages (Barkhuizen et al, 2017 ; Herrera et al, 2017 ; Herrera-Marschitz et al, 2017 ), such as the induction of PA at a time point when rodent brain maturity resembles the brain of a human fetus at 22–32 gestational weeks (Semple et al, 2013 ). This aspect is of clinical relevance since prematurity is associated with PA and increases the risk of neurological morbidity (Kuzniewicz et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…This aspect is of clinical relevance since prematurity is associated with PA and increases the risk of neurological morbidity (Kuzniewicz et al, 2014 ). In the last 26 years, this murine model contributed to scientific advances on the neuropathological, functional (Barkhuizen et al, 2017 ) and synaptic effects of PA on the CNS (Herrera et al, 2017 ), and on mechanisms of neuroprotection (Herrera-Marschitz et al, 2011 ; Muñiz et al, 2014 ). Research on neuroprotection is based on the concept of secondary lesion, which offers a therapeutic window for early intervention (Blanco et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Fifty-three male rat pups were subjected to PA using an experimental model (Bjelke et al, 1991), which produces moderate to severe PA (Van de Berg et al, 2003;Galeano et al, 2011) as we described previously (Capani et al, 2003(Capani et al, , 2009Saraceno et al, 2010Saraceno et al, , 2012aBlanco et al, 2015;Holubiec et al, 2017;Herrera et al, 2018). The murine model of PA, originally developed by Bjelke et al (1991), has been widely used (Barkhuizen et al, 2017;Herrera et al, 2017b) and accepted to mimic this condition (Capani et al, 1997(Capani et al, , 2003(Capani et al, , 2009Boksa and El-Khodor, 2003;Saraceno et al, 2010Saraceno et al, , 2012aStrackx et al, 2010;Muñiz et al, 2014;Romero et al, 2015;Wakuda et al, 2015;Herrera et al, 2018). The Bjelke model presents several advantages such as follows: (a) asphyxia is produced at birth (Capani et al, 2009); (b) acidosis, hypercapnia, and hypoxia are present in the whole body, replicating a global asphyxia, which is the most common type (Strackx et al, 2010); (c) it is non-invasive, avoiding the effects of surgical procedures; and (d) since hypoxia is produced in the whole body, it affects both brain hemispheres, which makes this model more suitable for behavioral studies (Arteni et al, 2010).…”
Section: Induction Of Pamentioning
confidence: 99%